Foreign language instructors' test practice: how and what to test? - Chan, Swee Heng; Esmeralda, Borges (Malaysian Association of Modern Languages, 2012)
Learning and teaching a foreign language in Universiti Putra Malaysia (UPM) is a relatively new experience. Relating to this experience is the concern for assessment which has two primary purposes, they are, to demonstrate to others that students are performing as expected and secondly to monitor student’s progress in order to plan appropriate actions. In the context of foreign language learning in UPM, the assessment practices are at a developmental stage and different test practices are likely to exist. The study intends to investigate the testing approaches adopted by the language instructors for the 13 foreign languages offered in UPM. An effort is made to look into similarities and differences in test practices to arrive at common baselines that may be used as bench markers for more rigorous test practice. Sample test papers were analysed to enable the researchers to obtain primary information about test intentions. A questionnaire and interview followed to provide further data as to the test design, areas of emphasis and reactions to perceived importance to certain domains of learning. Sample items are forwarded to illustrate recommended test practices for the assessment of foreign languages. The study could lead to standardisation in test practice and the provision of guidelines to students for self assessment which in turn could lead to greater learning autonomy.